2012
DOI: 10.2967/jnumed.111.101675
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 68Ga-DOTATATE PET/CT in Suspected Neuroendocrine Tumors

Abstract: In patients with suspected but yet not localized neuroendocrine tumors (NETs), early diagnosis or reliable exclusion is crucial for optimal individual prognosis and therapy. Despite recourse to several imaging modalities, the definite diagnosis of NET can be challenging. Therefore, we tested 68 Ga-DOTATATE PET/CT as a tool for improved diagnosis in a cohort of patients with suspected, nonlocalized NET. Methods: 68 Ga-DOTATATE PET/CT recordings were obtained in 104 consecutive patients meeting at least one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
92
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(96 citation statements)
references
References 30 publications
3
92
0
1
Order By: Relevance
“…Detection of a higher number of lesions is nevertheless not always followed by a change in disease stage and, most importantly, does not always affect the therapeutic approach. Although several studies have demonstrated the clinical impact of 68 Ga-DOTA peptides, few have compared the clinical impact of both PET tracers in NET patients (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of a higher number of lesions is nevertheless not always followed by a change in disease stage and, most importantly, does not always affect the therapeutic approach. Although several studies have demonstrated the clinical impact of 68 Ga-DOTA peptides, few have compared the clinical impact of both PET tracers in NET patients (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the better sensitivity, spatial resolution, and inherently quantitative nature of PET, somatostatin receptor imaging (SRI) with PET is increasingly used. Most common is the use of the 68 Ga-labeled somatostatin analogs, for example, 68 Ga-DOTATATE (6)(7)(8)(9), 68 Ga-DOTATOC (10)(11)(12), and 68 Ga-DOTANOC (13). However, the high positron energy of 68 Ga limits spatial resolution and the short half-life of 68 min may be challenging logistically, because production has to be aligned with patients and to be repeated several times a day.…”
mentioning
confidence: 99%
“…68 Ga-DOTATATE has a high affinity for sst 2(a) , 68 Ga-DOTATOC has a high affinity for sst 2(a) and sst 5 and 68 Ga-DOTANOC is sst 2(a) , sst 3 and sst 5 specific (13,31,32,33,34). Somatostatin receptor PET/CT using 68 Ga-DO-TANOC, 68 Ga-DOTATATE or 68 Ga-DOTATOC is superior to SRS SPECT-CT showing higher sensitivities for GEP-NET lesion detection (more than 90%), particularly due to a better special resolution or better sst affinities (13,31,32,33,34). These compounds are also more 'patient friendly', as they allow for imaging 1-3 h within i.v.…”
mentioning
confidence: 99%
“…Three different 68 Ga-DOTA-labelled SSAs are used in clinical practice: DOTANOC, DOTATATE and DOTATOC (13,31,32,33,34). These compounds differ with regard to their individual affinity for the different ssts.…”
mentioning
confidence: 99%
See 1 more Smart Citation